2022
DOI: 10.3390/healthcare10020363
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Prevalence of Depression and Antidepressants in the Spanish Population

Abstract: Introduction: Depression is a mental disorder that affects more than 250 million people in the world, limiting their functional capacities. The work of public health policies is aimed at reducing its prevalence as well as its pharmaceutical cost. Physical activity (PA) programs are interventions with a high potential for effectiveness. Objectives: To establish the relationships between physical activity and the prevalence of depression and antidepressant intake in the Spanish population. Design: We performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…In relation to other research, Galán-Arroyo et al highlighted that, in the general population, the prevalence of depression and anxiety were associated with the frequency of PA. The highest levels of prevalence of depression were also found in the population that “never” performs PA (13.4%), however, these data were slightly lower than in the present study, as the main difference lay in the fact that they studied the general population, as opposed to the condition of being a smoker or ex-smoker in the present study [ 42 ]. This study by Galán-Arroyo et al also shows that there is a lower prevalence of depression in the “active” population, which is noteworthy as they have lower prevalence data than the “very active” population, as in our study.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In relation to other research, Galán-Arroyo et al highlighted that, in the general population, the prevalence of depression and anxiety were associated with the frequency of PA. The highest levels of prevalence of depression were also found in the population that “never” performs PA (13.4%), however, these data were slightly lower than in the present study, as the main difference lay in the fact that they studied the general population, as opposed to the condition of being a smoker or ex-smoker in the present study [ 42 ]. This study by Galán-Arroyo et al also shows that there is a lower prevalence of depression in the “active” population, which is noteworthy as they have lower prevalence data than the “very active” population, as in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…In both sub-study 1 and sub-study 2, in smokers and ex-smokers, a higher prevalence of depression (9.4–15.7% vs. 6.8–9.1%) and anxiety (11.4–16.3% vs. 5.8–7.9%) was found in women compared to men. Another study in the general population also found a higher prevalence of depression in women (12.5%) than in men (6.2%), in this case twice as high [ 42 ].…”
Section: Discussionmentioning
confidence: 87%
“…Depression prevalence was higher in the inactive groups, decreasing in the groups with higher PA frequency. Several studies support these results [ 15 , 16 , 37 , 38 ], stating that is mandatory to increase the importance of PA to reduce the likelihood of depression. Rosenbaum (2014) [ 22 ] reported that PA reduces depressive symptoms in people with mental illness.…”
Section: Discussionmentioning
confidence: 78%
“…Some examples of these policies could be guides and advice for families about PA, sports programs promoted by municipalities, educational centers and companies, policies to promote PA as a way of transportation, creating areas for the practice of PA, active aging programs, etc. These policies are aimed to increase the frequency of PA in all age groups, as inactivity has a potential risk for depression [ 15 , 16 ], and as we know, depression can appear at any age [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation